Otimização e avaliação multivariada na obtenção, purificação e caracterização de biossurfactante obtido por bioreação do Bacillus subtilis ATCC 9372 utilizando melaço de cana-de-açúcar - Maroldi, Wédisley Volpato (2018)
Over the years and numerous researches in the biotechnology area biosurfactants began to be synthesized by a range of microorganisms that, acting on a carbon source, and aided by a source of nitrogen and minerals, produce compounds with superior characteristics when compared to synthetic surfactants. Its uses have been expanded, but the production cost of biosurfactants is still high when compared to synthetic surfactants. In this sense, research that contributes to the improvement of bioprocess production of biosurfactants is necessary. In this work, the chemometric tools of multivariate experimental design were of fundamental importance to optimize the experimental conditions. The Doehlert experimental design contributed in the optimization of the acid type and its experimental conditions for the hydrolysis of sugarcane molasses. The results indicated that 10% sulfuric acid with a reaction time of 60 minutes provides an increase in the concentration of reducing sugars. The clarification step of hydrolyzed molasses (MH) was optimized through factorial design 22. Clarification using lead subacetate and ultrafiltration were considered in the biosurfactant production stage. Throughout the bioprocess the growing formation of the biosurfactant and a reduction in the amount of reducing sugars were observed. A statistical evaluation showed a significant difference at the beginning of the bioprocess made from MH clarified with lead subacetate and from MH clarified by ultrafiltration. However, the difference is not statistically significant, at the 99% level, at the end of the bioreaction. PCA, applied to data fusion of NIR spectroscopy and laboratory results for biomass, product, protein and reducing sugar, allowed to explore the bioprocess in a more objective way. It was possible to infer about the formation of biosurfactant until the time of 108 hours of bioreaction when a stabilization occurs in the bioprocess. Moreover, until 60 hours of bioreaction, the variables that have the significant influence on the bioprocess are the reducing sugar and absorptions in the NIR region corresponding to the second overtone of the CH, CH2, CH3, and ArOH between 1200-1400 nm, and to the first overtone of the ArCH around 1600 nm. After 72 hours of bioprocess, the variables that most influence bioreaction are biomass and the product. These variables are correlated with NIR regions between 900-1100 nm (absorption of the third overtone of CH, CH2, CH3, ArOH, ROH, H2O, RNH2 and ArCH) and 1400-1500 nm (absorptions of the second overtone of CH bonds CH2, CH3, CONHR, ArOH, ROH, H2O, RNH2 and CONH2). The bubbling performed in 3 steps increased the product concentration and presented a statistically significant difference, at the 95% level, in the Tukey test.